Penurunan Nitrat Pada Air Limbah Domestik dengan Air-Lift Photobioreactor Berbasis Mikroalga - Acbellita Ayu Zevhiana; Tuhu Agung Rachmanto (Jurnal Serambi Engineering, 2024)
Domestic wastewater often contains nutrients that can potentially cause environmental problems if released into the environment without proper treatment. One of the nutrients that needs to be managed is nitrate, which can be used as a nutrient source for microalgae in an air-lift photobioreactor (AL-PBR). The aim of this study was to test the efficiency of nitrate removal from domestic wastewater using the microalgae Chlorella vulgaris and AL-PBR. The cultivation of microalgae was carried out in a culture medium containing deionised water and F2 Guillard nutrients for 7 days with full lighting and aeration. The acclimatisation phase was carried out for 7 days with a gradual addition of wastewater to prepare the microalgae for real environmental conditions. Analysis showed that pH and temperature during cultivation and acclimatisation were within safe ranges for the microalgae. The highest nitrate removal occurred with 80% wastewater treatment using blue light (λ=440 nm), achieving a removal percentage of 97.49%, indicating that wastewater concentration affects nitrate removal efficiency. These results provide importantinsights into the potential use of microalgae and AL-PBR in domestic wastewater treatment to support efforts to maintain the quality of aquatic environments.